2016
DOI: 10.2298/sarh1602038s
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial/experimental study (consort compliant): Optimal time period to achieve the effects on synbiotic-controlled wheezing and respiratory infections in young children

Abstract: The optimal duration of administration of the synbiotic containing three probiotic cultures to provide effective control of the frequency of respiratory infections was three months, and six months were required to establish control of the frequency of wheezing. This synbiotic is useful for immunomodulation in children and is well-tolerated in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…We have, also, confirmed that the use of synbiotics in the optimal period of time of 3-6 months can achieve adequate control of respiratory infection and allergic wheezing diseases in children younger than 5 years [34]. Nevertheless, we have found that the time necessary for the restitution of the immune balance between immunoglobulin A and immunoglobulin E was 9 months in the youngest children [34]. Now, we can add a logical setting as hypothesis that should have been assessed in clinical trials, that the everyday application of synbiotic (during several months) after antibiotic using would likely prevent the obesity.…”
Section: The Obese and Asthmatic Children Treated With Antibioticssupporting
confidence: 68%
See 2 more Smart Citations
“…We have, also, confirmed that the use of synbiotics in the optimal period of time of 3-6 months can achieve adequate control of respiratory infection and allergic wheezing diseases in children younger than 5 years [34]. Nevertheless, we have found that the time necessary for the restitution of the immune balance between immunoglobulin A and immunoglobulin E was 9 months in the youngest children [34]. Now, we can add a logical setting as hypothesis that should have been assessed in clinical trials, that the everyday application of synbiotic (during several months) after antibiotic using would likely prevent the obesity.…”
Section: The Obese and Asthmatic Children Treated With Antibioticssupporting
confidence: 68%
“…It has been proven that "good" probiotic bacteria and "good" probiotic fungi in the mouth and intestines, sufficiently represented, are necessary to compensate destroyed intestinal flora during and after antibiotic therapy and for the health of children [5] ( Figure 1). We have, also, confirmed that the use of synbiotics in the optimal period of time of 3-6 months can achieve adequate control of respiratory infection and allergic wheezing diseases in children younger than 5 years [34]. Nevertheless, we have found that the time necessary for the restitution of the immune balance between immunoglobulin A and immunoglobulin E was 9 months in the youngest children [34].…”
Section: The Obese and Asthmatic Children Treated With Antibioticssupporting
confidence: 65%
See 1 more Smart Citation
“…According to the literature, application of probiotics or synbiotic treatment regimens in respiratory infections reduces relapse respiratory tract infections and bronchial obstruction in children [9]. But the authors did not conduct any studies to determine the number of lactobacilli in secrets of URt and their influence on anti-infectious resistance of mucous membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics based on lactobacilli are widely used to prevent and treat dysbiotic conditions of digestive and genital human system [6][7][8]. Nowadays, research on the use of lactobacilli for prevention or treatment of infections and recovery of anti-infectious resistance of mucous membranes of upper respiratory tract (URT) are actual [9].…”
Section: Introductionmentioning
confidence: 99%